Antimicrobial Activity Of Extracellularly Synthesized Silver Nanoparticles From Marine Derived Streptomyces Rocheiv - P.SELVAKUMAR; S.VIVEKA; S.PRAKASH; S.JASMINEBEAULA; R.ULOGANATHAN (International Journal of Pharma and Bio Sciences, 2012)
The process of development of reliable and eco-friendly metallic nanoparticles is an important step in the field of nanotechnology. To achieve this use of natural sources like biological systems becomes essential. In the present work, we have investigated extracellular biosynthesis of silver nanoparticles at two molar concentrations (10-3 and 10-4) of AgNO3 using Streptomyces rochei isolated from the marine sediment samples of Kanyakumari Coast , Tamil Nadu , India. The silver nanoparticles were analyzed by UV-Visible spectroscopy. The antimicrobial activities of silver nanoparticles were screened against common human pathogen Pseudomonas aeruginosa, E.coli, Klebsiella pneumoniae, Enterobactor faecalis and Staphylococcus aureus. The results showed silver nanoparticles synthesized at 10-4 molar concentration of AgNO3 displayed a significant antibacterial activity against S. aureus and P. aeruginosa. This study gives an innovative approach to develop new formulations based on metallic nanoparticles with antimicrobial properties to reach the pharmaceutical companies searching for new unconventional antibacterial agents.